Long chain saturated and unsaturated fatty acids exert opposing effects on viability and function of GLP-1-producing cells: Mechanisms of lipotoxicity - Thombare, Ketan (PLoS One, 2017)
BACKGROUND AND AIM: Fatty acids acutely stimulate GLP-1 secretion from L-cells in vivo. However, a high fat diet has been shown to reduce the density of L-cells in the mouse intestine and a positive correlation has been indicated between L-cell number and GLP-1 secretion. Thus, the mechanism of fatty acid-stimulated GLP-1 secretion, potential effects of long-term exposure to elevated levels of different fatty acid species, and underlying mechanisms are not fully understood. In the present study, we sought to determine how long-term exposure to saturated (16:0) and unsaturated (18:1) fatty acids, by direct effects on GLP-1-producing cells, alter function and viability, and the underlying mechanisms. METHODS: GLP-1-secreting GLUTag cells were cultured in the presence/absence of saturated (16:0) and unsaturated (18:1) fatty acids (0.125 mM for 48 h, followed by analyses of viability and apoptosis, as well as involvement of fatty acid oxidation, free fatty acid receptors (FFAR1) and ceramide synthesis. In addition, effects on the expression of proglucagon, prohormone convertase 1/3 (PC1/3), free fatty acid receptors (FFAR1, FFAR3), sodium glucose co-transporter (SGLT) and subsequent secretory response were determined. RESULTS: Saturated (16:0) and unsaturated (18:1) fatty acids exerted opposing effects on the induction of apoptosis (1.4-fold increase in DNA fragmentation by palmitate and a 0.5-fold reduction by oleate; p<0.01). Palmitate-induced apoptosis was associated with increased ceramide content and co-incubation with Fumonisin B1 abolished this lipo apoptosis. Oleate, on the other hand, reduced ceramide content, and—unlike palmitate—upregulated FFAR1 and FFAR3, evoking a 2-fold increase in FFAR1-mediated GLP-1 secretion following acute exposure to 0.125 mmol/L palmitate; (p<0.05). CONCLUSION/INTERPRETATION: Saturated (16:0), but not unsaturated (18:1), fatty acids induce ceramide-mediated apoptosis of GLP-1-producing cells. Further, unsaturated fatty acids confer lipoprotection, enhancing viability and function of GLP-1-secreting cells. These data provide potential mechanistic insight contributing to reduced L-cell mass following a high fat diet and differential effects of saturated and unsaturated fatty acids on GLP-1 secretion in vivo.